Cross-species transcriptomics identifies core regulatory changes differentiating the asymptomatic asexual and virulent sexual life cycles of grass-symbiotic Epichloë fungi. Issue 4 (22nd February 2022) - Berry, Daniel; Lee, Kate; Winter, David; Mace, Wade; Becker, Yvonne; Nagabhyru, Padmaja; Treindl, Artemis D; Bogantes, Esteban Valverde; Young, Carolyn A; Leuchtmann, Adrian; Johnson, Linda J; Johnson, Richard D; et al.
Abstract: Fungi from the genus Epichloë form systemic endobiotic infections of cool season grasses, producing a range of host-protective natural products in return for access to nutrients. These infections are asymptomatic during vegetative host growth, with associations between asexual Epichloë spp. and their hosts considered mutualistic. However, the sexual cycle of Epichloë spp. involves virulent growth, characterized by the envelopment and sterilization of a developing host inflorescence by a dense sheath of mycelia known as a stroma. Microscopic analysis of stromata revealed a dramatic increase in hyphal propagation and host degradation compared with asymptomatic tissues. RNAseq was used to identify differentially expressed genes in asymptomatic vs stromatized tissues from 3 diverse Epichloë –host associations. Comparative analysis identified a core set of 135 differentially expressed genes that exhibited conserved transcriptional changes across all 3 associations. The core differentially expressed genes more strongly expressed during virulent growth encode proteins associated with host suppression, digestion, adaptation to the external environment, a biosynthetic gene cluster, and 5 transcription factors that may regulate Epichloë stroma formation. An additional 5 transcription factor encoding differentially expressed genes were suppressed during virulent growth, suggesting they regulate mutualistic processes. Expression of biosynthetic gene clusters for natural products that suppress herbivory was universally suppressed during virulent growth, and additional biosynthetic gene clusters that may encode production of novel host-protective natural products were identified. A comparative analysis of 26 Epichloë genomes found a general decrease in core differentially expressed gene conservation among asexual species, and a specific decrease in conservation for the biosynthetic gene cluster expressed during virulent growth and an unusual uncharacterized gene.